Children's Education and Parents' Trajectories of Depressive Symptoms. (March 2017) - Lee, Chioun; Glei, Dana A.; Goldman, Noreen; Weinstein, Maxine
Using five waves of the Taiwanese Longitudinal Study of Aging (1996–2011), we investigate (1) the association between family members' education and the age trajectories of individuals' depressive symptoms and (2) gender differences in those relationships. Our examination is guided by several theoretical frameworks, including social capital, social control, age as leveler, and resource substitution. Nested models show that having a more educated father is associated with lower depressive symptoms, but the relationship disappears after controlling for respondent's education. Including spouse's education attenuates the coefficient for respondent's education. A similar pattern appears when children's education is added to the model. Among all the family members, children's education has the strongest association with depressive symptoms, with a similar magnitude for both genders, although its strength gradually weakens as respondents age. Our findings suggest the importance of the transfer of resources from children to parents and how it may affect mental health at older ages.